Neurotoxic lesions of the anterior claustrum influence cued fear memory in rats - Gu, Tengyu; Dong, Jing; Ge, Jing; Feng, Jialu; Liu, Xiaoliu; Chen, Yun; Liu, Jianfeng (Frontiers in Psychiatry, 2024)
The claustrum (CLA), a subcortical area between the insular cortex and striatum, innervates almost all cortical regions of the mammalian brain. There is growing evidence that CLA participates in many brain functions, including memory, cognition, and stress response. It is proposed that dysfunction or malfunction of the CLA might be the pathology of some brain diseases, including stress-induced depression and anxiety. However, the role of the CLA in fear memory and anxiety disorders remains largely understudied. Here, we evaluated the influences of neurotoxic lesions of the CLA on auditory-cued fear memory and anxiety-like behaviors in rats.We found that lesions of anterior CLA (aCLA) but not posterior CLA (pCLA) before fear conditioning attenuated fear retrieval, facilitated extinction, and reduced freezing levels during the extinction retention test. Post-learning lesions of aCLA but not pCLA facilitated fear extinction and attenuated freezing behavior during the extinction retention test. Lesions of aCLA or pCLA did not affect anxiety-like behaviors evaluated by the open field test and elevated plus-maze test.These data suggested that aCLA but not pCLA was involved in fear memory and extinction.Future studies are needed to further investigate the anatomical and functional connections of aCLA subareas that are involved in fear conditioning, which will deepen our understanding of CLA functions.